Cardiac depressant and vasodialatory effect of flaxseed - basis for the medicinal use in hypertension - Palla, Amber Hanif; Ur Rehman, Najeeb; Siddiqi, Hasan Salman; Gilani, Anwar-Ul-Hassan; Siddiqui, Bina Shaheen; Ilyas, Maimoona; Perwaiz, Sobiya (Penerbit Universiti Kebangsaan Malaysia, 2021)
Linum usitatissimum (Flaxseed) is known to be traditionally used for managing hypertension. In this study, we aim to provide a mechanistic basis for the medicinal use of Flaxseed in hypertension. The high-performance liquid chromatography (HPLC) analysis that we carried out during our study showed the presence of polar compounds (quercetin, nicotinic acid, and nicotinamide) in Flaxseed’s crude extract (Fs.Cr; aqueous methanolic). In anesthetized rats, Fs.Cr reduced arterial blood pressure (BP) dose-dependently (10-100 mg/kg). When tested for its mechanism of action ex vivo, Fs.Cr inhibited both the force and rate of spontaneous contractions in the dose range of 1-10 mg/mL in isolated guinea-pig atria, similar to how verapamil, a standard Ca+2 channel blocker does it. Further, Fs.Cr showed vasodilator effect against the contractions induced by phenylephrine (PE, 1 μM) in rat aortic ring preparations (concentration range: 1-10 mg/mL), whereas no effect was observed against the contractions induced by low K+ (25 mM) as well as high K+ (80 mM). This selective inhibitory effect of Fs.Cr against PE was tested for endothelium-dependent nitric oxide (NO) and/or cholinergic component involvement. The vasodilator effect of Fs.Cr against PE was retested in the absence and presence of atropine in endothelium (E)-intact and E-denuded aorta, but no significant shift was observed in the inhibitory effect of Fs.Cr. Further, Fs.Cr shifted the PE-induced concentration-response curves (CRCs) to the right in a dose-dependent manner (1 and 3 mg/mL). This effect was similar to that of prazosin. All these findings indicate that Flaxseed may mediate its antihypertensive activity by the alpha-1 receptor antagonist and Ca+2 channel blocking-like activity, which may account for its efficacy in hypertension.